(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
In agriculture, weed control through chemical herbicides, creates spray drift hazards and adversely affects the environment. The search for an alternate method for the degradations of herbicides through the use of bacteria which is eco-friendly for the bioremediations of herbicides contaminated soil. This study aimed at assessing the biodegradation of glyphosate and paraquat herbicides by bacteria isolated from soil. Soil samples were collected from Research Farm of National Root Crops Research Institute, Ginger Station, Kajuru, Kaduna State, Nigeria. Bacteria were isolated and identified based on colonial and biochemical characteristics. The assessment for the potential of the bacterial isolates to degrade glyphosate and paraquat herbicides was carried out using microcosms study. The bacterial isolates were phenotypically identified as Proteus sp., Acidovorax sp., Micrococcus sp., Staphylococcus aureus, Bacillus sp. and Aeromonas sp. Among the isolates, Acidovorax sp. and Aeromonas sp. had the highest potential to utilize glyphosate and paraquat as sole source of carbon. In the presence of glyphosate Acidovorax sp. and Aeromonas sp. had cells count of 1.30×108cfu/g and 1.90×108cfu/g respectively. However, in the presents of paraquat as a source of carbon Acidovorax sp. and Aeromonas sp. had the counts of 1.90×107cfu/g and 2.60×106cfu/g respectively. The quantifications of glyphosate and paraquat herbicides residues in amended soil using GC/MS shows that Acidovorax sp. have degraded 77.1% while Aeromonas sp. 88.1% of glyphosate. However, Acidovorax sp. degraded 51.5% while Aeromonas sp. 59.8% of paraquat. This study showed that Acidovorax sp. and Aeromonas sp. had the potential to degrade glyphosate and paraquat herbicides.